As representações e os discursos dos professores sobre a EMEIEF Prada : entre o imaginário e o real - Moreira, Marisa de Souza Cunha (2016)
This work seeks to deduce the representations and discourses of teachers about Prada School, which is located in the countryside of São Paulo and was founded by private capital in 1947 in order to assist the children of industrial workers. The school was donated to the public authorities in 1954 and municipalized in 2000. The guiding problem consists of investigating how the school is understood by the teachers participating in the research, once, in the collective imaginary, the institution is generally regarded as a differentiated school in relation to various educational units in the town. Its origin (in the industry) was considered to be different from the other schools belonging to its same system; and it was sought to analyze the causes of its foundation and the aspects of constructing its identity in the social imaginary. The central goal, guided by reflections on the relations between work and education, was to identify teachers and managers‘ views about social representations and about training and educational processes related to EMEIEF Prada. The specific goals was to: analyze the concepts attributed by teachers and managers to the educational practices and to their meanings in their professional career; identify the real and symbolic aspects related to the foundation and development of this school by considering the social construction of its identity and its recognition in the public school system. The methodological procedure, which makes use of a qualitative approach, includes documentary, bibliographic and field research, with emphasis on semi-structured interviews with teachers and managers. The analysis of the interviews revealed that the social representations of teachers agree with those belonging to the general population in many cases; it also revealed that the school has over the years kept the imaginary of being a differentiated school. One of the aspects of the researched school was its central localization. This fact contributes to it being seen as a school with a qualified education and with a differentiated public, generally opposed to the characteristics of the public schools of the periphery, despite there being similarities. It is concluded that the representations and discourses about the school combine real and imaginary elements regarding its history and practices, which interconnect and influence each other, in order to reinforce idealized and aimed aspects in its history and daily routine. Thus, discourses that exalt their particularities and supposed experience permeated by feelings of pride or a certain nostalgia are reproduced.